2018
DOI: 10.1016/j.amepre.2017.12.016
|View full text |Cite
|
Sign up to set email alerts
|

The Affordability of Providing Sexually Transmitted Disease Services at a Safety-net Clinic

Abstract: Introduction Sexually transmitted diseases continue to increase in the U.S. There is a growing need for financially viable models to ensure the longevity of safety-net sexually transmitted disease clinics, which provide testing and treatment to high-risk populations. This micro-costing analysis estimated the number of visits required to balance cost and revenue of a sexually transmitted disease clinic in a Medicaid expansion state. Methods In 2017, actual and projected cost and revenues were estimated from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Even so, as mentioned previously, STD clinics are beginning to bill for Medicaid services in order to cover their costs. 14 Because of this, researchers may wish to investigate whether patients seeking care in STD clinics receive comparable care to those who seek STD care in community-based physician offices. Stake-holders should monitor U.S. healthcare system reforms, including amendments to the eligibility standards of Medicaid (or other public programs), in a way that broadens the program to additional populations, for how they affect the rate of people being uninsured, and ultimately, access to STD services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, as mentioned previously, STD clinics are beginning to bill for Medicaid services in order to cover their costs. 14 Because of this, researchers may wish to investigate whether patients seeking care in STD clinics receive comparable care to those who seek STD care in community-based physician offices. Stake-holders should monitor U.S. healthcare system reforms, including amendments to the eligibility standards of Medicaid (or other public programs), in a way that broadens the program to additional populations, for how they affect the rate of people being uninsured, and ultimately, access to STD services.…”
Section: Discussionmentioning
confidence: 99%
“…1012 It is possible that recent healthcare system changes have affected the financing and delivery of STD care, particularly in public clinics and among populations at increased risk for STDs. 13,14…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 11 million Americans have insurance coverage as of February 2018 through the exchange programs (Henry J. Kaiser Family Foundation, ). Through these insurance programs access to preventive health care and the requirement for insurance plans to cover, in some populations, with no co‐pays for HIV, syphilis, gonorrhea, and chlamydia testing are all provisions in the ACA (Dean et al, ). While these reforms increase insurance availability, they also offer significant opportunities for public health agencies to bill for STD services that have previously been billed to Medicaid only or provided for free.…”
Section: Introductionmentioning
confidence: 99%
“…While these reforms increase insurance availability, they also offer significant opportunities for public health agencies to bill for STD services that have previously been billed to Medicaid only or provided for free. One study suggested publicly funded STD clinics might not be fiscally sound when billing Medicaid only but could be financially viable if other types of private insurance reimbursement were available (Dean et al, ). Public health agencies face the constant challenges of decreasing budgets and mounting service needs which escalates the importance of developing a billing strategy to sustain services (McCullough, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation